The (un)translatability of Qur'anic idiomatic phrasal verbs - Dahish, ʻAlī Yūnus, author.
1 online resource.
Keywords: "Qur'anic idiomaticity, in its all aspects, poses a great deal of challenge to the Qur'an readers, learners, commentators and translators. One of the most challenging aspects of the Qur'anic idiomaticity is Qur'anic Idiomatic Phrasal Verbs, where significances of proper Arabic verbs are entirely fused into significances of prepositions following them to produce new significances, which have nothing to do with the basic significances of those verbs and prepositions. By examining a corpus of ten of the most influential English translations of the Qur'an, this study scrutinises the ways by which translators of the Qur'an deal with the phenomenon of Qur'anic Idiomatic Phrasal Verbs, difficulties they encounter when translating them into English, strategies they employ in their attempt to overcome the inherent ambiguity of such expressions and provide their functional-pragmatic equivalent to English readership. The study proposes a working model for analysing and assessing translation of the Qur'anic Idiomatic Phrasal Verbs and provides a number of theoretically based recommendations for translators in general and the Qur'an translators in particular"--